(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
The central problem addressed in this study arises from the apparent imbalance in prosperity teachings, which often place greater emphasis on material and physical well-being than on the primary message of salvation and discipleship. The primary objectives of this study are to identify and analyze the four cardinal dimensions of prosperity as taught in Dunamis Church, to appraise their theological and biblical foundations, and to assess their impact on the spiritual and social lives of members and the broader society. The research adopted a qualitative methodology, utilizing a case study approach that combined doctrinal analysis, textual interpretation, and review of relevant theological literature. The study is grounded in the Prosperity Theology framework, which posits that faith, positive confession, and covenant obedience are the keys to comprehensive and all inclusive prosperity. The findings reveal that Dunamis Church presents a complete view of prosperity that incorporates spiritual growth, financial achievement, social influence, and overall well being. While this comprehensive approach has empowered many faithful economically and socially, it also risks promoting the problematic teaching that God’s blessings are measured solely by material achievements. The study discovers that placing excessive emphasis on material achievements may unconsciously weaken Christian values of humility, service, and redemptive suffering. Through case studies and interdisciplinary insights, the study concludes that Prosperity theology as taught and practiced in Dunamis Church encompasses both strengths and weaknesses. Its emphasis on faith, productivity, and human flourishing aligns with the biblical vision of abundant life, yet it requires theological balance to maintain the preeminence of spiritual transformation over material achievement. The study recommends that theologians and preachers of the Gospel should communicate messages that emphasize a more Christocentric understanding of prosperity, one that incorporates salvation, stewardship, and social responsibility. It also calls for profound theological education among Prosperity Gospel preachers to teach the Gospel that promotes both spiritual maturity and social justice in the Church.